2019
DOI: 10.1016/s2213-8587(19)30084-1
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and ectopic fat, atherosclerosis, and cardiometabolic disease: a position statement

Abstract: Findings from epidemiological studies over the past 30 years have shown that visceral adipose tissue, accurately measured by CT or MRI, is an independent risk marker of cardiovascular and metabolic morbidity and mortality. Emerging evidence also suggests that ectopic fat deposition, including hepatic and epicardial fat, might contribute to increased atherosclerosis and cardiometabolic risk. This joint position statement from the International Atherosclerosis Society and the International Chair on Cardiometabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
676
5
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 884 publications
(737 citation statements)
references
References 111 publications
21
676
5
35
Order By: Relevance
“…This definition is meaningless, however, due to the lack of established guidelines related to the visceral and subcutaneous adipose tissue [1]. A recent position statement on obesity claims the need for public health messaging to focus on visceral and ectopic fat, in addition to excess bodyweight to better combat the growing obesity epidemic worldwide [2]. Body changes in the elderly involve the loss of lean body mass while fat mass may be preserved or even increased in two different directions (visceral or subcutaneous), thereby giving rise to the specific condition of sarcopenic obesity [3].…”
Section: Introductionmentioning
confidence: 99%
“…This definition is meaningless, however, due to the lack of established guidelines related to the visceral and subcutaneous adipose tissue [1]. A recent position statement on obesity claims the need for public health messaging to focus on visceral and ectopic fat, in addition to excess bodyweight to better combat the growing obesity epidemic worldwide [2]. Body changes in the elderly involve the loss of lean body mass while fat mass may be preserved or even increased in two different directions (visceral or subcutaneous), thereby giving rise to the specific condition of sarcopenic obesity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Faris et al reported that serum levels of adiponectin, IL-6, TNF-a, and insulin-like growth factor-1 were significantly decreased. However, there was a significant increase in the serum levels of visfatin, leptin, apelin, and IL-10, at the end of Ramadan (71,72). Previous studies have reported contradictory results regarding the effect of diurnal IF on leptin levels.…”
Section: Effects On Inflammatory Biomarkersmentioning
confidence: 84%
“…At the end of Ramadan, visceral fat tissue area, weight, and systolic blood pressure were significantly decreased compared to the baseline (70). Visceral adiposity has been shown to have a significant association with cardiometabolic risk, even in non-obese individuals (71,72). Moreover, Faris et al reported that serum levels of adiponectin, IL-6, TNF-a, and insulin-like growth factor-1 were significantly decreased.…”
Section: Effects On Inflammatory Biomarkersmentioning
confidence: 99%
“…Очень интересные исследования, выполненные в популяции индейцев Пима, имеющих наибольший риск СД2, показали, что низкая секреция инсулина и высокая степень инсулинорезистентности независимо друг от друга предсказывали повышенный риск СД2 [12,13]. Кроме того, увеличение содержания висцерального жира и повышенное отложение жира в печени ассоциированы с повышенным риском СД2 и ССЗ [14,15].…”
Section: фенотипы предиабета и риск сахарного диабета 2 типа и сердечunclassified